2010
DOI: 10.4315/0362-028x-73.12.2296
|View full text |Cite
|
Sign up to set email alerts
|

SaniTwice: A Novel Approach to Hand Hygiene for Reducing Bacterial Contamination on Hands When Soap and Water Are Unavailable

Abstract: The risk of inadequate hand hygiene in food handling settings is exacerbated when water is limited or unavailable, thereby making washing with soap and water difficult. The SaniTwice method involves application of excess alcohol-based hand sanitizer (ABHS), hand "washing" for 15 s, and thorough cleaning with paper towels while hands are still wet, followed by a standard application of ABHS. This study investigated the effectiveness of the SaniTwice methodology as an alternative to hand washing for cleaning and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…However, hand washing with soap is more effective in reducing the prevalence of contamination and specifically of Enterococcus spp (Burton et al, 2011). On the other hand, ABHS is significantly better than hand washing at reducing levels of Escherichia coli (Edmonds et al, 2010) and fecal streptococci (Pickering, Boehm, Mwanjali, & Davis, 2010). To our knowledge, data about the efficacy of soap and alcoholbased products to reduce Bacteroidales in hands is very limited or not available.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, hand washing with soap is more effective in reducing the prevalence of contamination and specifically of Enterococcus spp (Burton et al, 2011). On the other hand, ABHS is significantly better than hand washing at reducing levels of Escherichia coli (Edmonds et al, 2010) and fecal streptococci (Pickering, Boehm, Mwanjali, & Davis, 2010). To our knowledge, data about the efficacy of soap and alcoholbased products to reduce Bacteroidales in hands is very limited or not available.…”
Section: Introductionmentioning
confidence: 99%
“…One hand hygiene intervention that may inactivate and remove microbes despite soiled hands is SaniTwice™, a two-step technique where an excess of ABHS is applied to hands and removed with paper towels, followed by a second, normal volume ABHS application (Edmonds et al, 2010). SaniTwice™ has been shown to reduce E. coli on hands soiled with beef broth and raw hamburgers (Edmonds et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally boot dips should be used in conjunction with a boot change for entry into each individual house, since no disinfectant is likely to be effective within the few seconds that it takes to enter a poultry house (Allen & Newell, 2005;Edmonds et al, 2010). Dips should not be prepared or used in metallic containers and not be used if past their expiry date.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of AHRs compared with water and soap has been investigated extensively in experimental studies (Edmonds et al, 2010;Hobson et al, 1998;Kampf et al, 1999). These studies have shown a clear reduction in the number of c.f.u.…”
Section: Introductionmentioning
confidence: 99%